Peningkatan Pertumbuhan Beberapa Varietas Bawang Merah Akibat Pemberian POC Bonggol Pisang Plus - Luta, Devi Andriani; Sitepu, Sri Mahareni Br.; Mutia, Hanifah; Daulay, Alzi Zikri (JURNAL AGROPLASMA, 2022)
Shallots are a leading commodity where shallots are a food security commodity. This study aims to determine the increase in the growth of several varieties of shallots. This study used a factorial randomized block design consisting of 2 treatment factors, namely several varieties of shallots (V) consisting of super philip, bauji, bima and maja cipanas. POC banana weevil plus (P) consisting of 0 ml/liter water/plot, 150 ml/liter water/plot, 300 ml/liter water/plot, 450 ml/liter water/plot Plant observations included leaf length (cm), number of leaves (strands), number of tillers per clump (saplings). The results showed that several shallot varieties experienced an increase in plant height, number of leaves and number of tillers. Where the best varieties are majacipanas (plant height) and bima varieties (number of leaves).Â Keywords: banana weevil plus, growth, poc, varieties